Design and fabricated pump trolley - Muhammad Badrul, Ishak Mustafa (2013)
In this modern era, so the pump is used in our daily activities whether at home or in industries. However, the difficulty to bring the pump from one place to another place is difficult because of the heavy pumps. This problem has led to produce a special trolley pump special for the pump. There are several steps that must be taken to design and produce a pump trolley. To get something good, the design of a product is important. Several designs have been developed based on the desired characteristics. The concept has been used for the selection of appropriate design to problems encountered. Drawing three-dimensional structure has been developed to facilitate the process of measuring and producing products. This three-dimensional drawings were produced with software engineering drawings "Solidworks". Fabrication process has undergone steps such as measuring, marking, cutting, welding, drilling and finally paint product. In conclusion, the objective of the trolley pump design that fulfill the criteria were reached. Results are also able to reduce costs, improve customer trust and confidence in this product.